THE INFLUENCE OF CHILDREN’S LITERATURE ON THE FORMATION AESTHETIC CULTURE OF A PRESCHOOL CHILD - Onyshchenko, I.V. (Pedagogy of Higher and Secondary Education, 2008)
The article describes since of aesthetic education of pre-school children, defines the role of child’s literature in forming culture of preschool children.